PRODUCTION OF SILVER NANOPARTICLE FROM CHLORELLA VULGARIS AND DUNALIELLA SALINA - Hermin P. Kusumaningrum; Muhammad Zainuri; Indras Marhaendrajaya (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Green microalgae have advantages as they are easily available, grow rapidly and produce various secondary metabolites including carotenoids, fatty acids, proteins and lipids. Synthesis of nanosilver microalgae C. vulgaris and D. salina offers environmental antimicrobial and biomedical agent. The objective of this study was to produce silver nanoparticle (SNP) microalgae using C. vulgaris and D. salina as an eco-friendly antimicrobial agent. This research method was conducted by synthesizing silver nanoparticle microalgae using C. vulgaris and D. salina along with characterization under UV–visible spectroscopy, transmission electron microscopy (TEM), and scanning electron microscope (SEM) and Energy-dispersive X-ray spectroscopy (EDX). The results showed that SNP of C. vulgaris and D. salina microalgae could be produced using agitation treatments. The synthesized AgNPs C. vulgaris and D. salina exhibited maximum absorption at 398 nm, and EDX analysis had determined that the abundance of chemical elements presented in the sample is carbon (53 %) and silver (32 %). TEM analysis revealed that they had spherical form with a size of 9.3 nm. The spot of EDX analysis shows the presence of silver atoms in both microalgae. SEM analysis shows a spherical shape with an average size of 50 nm with several silver particles in the cell. These results indicate that the formation of SNP using C. vulgaris and D. salina microalgae has been successfully obtained under agitation treatment.